Analysis of Facility and Infrastructure Management of Hapkido Lampung: An Observational Study - Tiara Chandra Kirani; Berlian Chandra Kirana; Aghus Sifaq (Universitas Negeri Semarang, 2026)
Sports facilities are a determining factor in the success of athlete development. This study aims to analyze the condition of training facilities, completeness of infrastructure, and the management system applied at the Hapkido Lampung facility located at BTC Gym Seputih Raman, Central Lampung Regency. The method used was direct observation conducted on March 21, 2026. The observation focused on building infrastructure, training areas on the 1st and 2nd floors, gym facilities, athlete dormitories, CCTV security systems, business strategy, and sanitation facilities. The results show that BTC Gym Hapkido Lampung facilities are generally adequate and suitable for supporting athlete development. The training building has a spacious area, adequate ventilation, sufficient lighting, and training mats that support athlete safety. The gym is equipped with diverse fitness equipment covering strength, endurance, and cardiovascular training. The athlete dormitory has 6 rooms, 5 bathrooms, a kitchen, washing machine, and first-aid facilities. The security system uses 11 CCTV units installed throughout the training area. However, several aspects require improvement, including manual inventory management, inconsistent facility maintenance, and minimal integration of digital technology in the management system. Recommendations include digitalization of the management system, regular facility maintenance, and development of cooperation with local governments and sports organizations.